Public Complaints Information System at Jentera Stabat Village Office - Melia Pradita; Raheliya Br. Ginting; Siti Jamilah Br. Tarigan; Ita Margaretta Br. Tarigan (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
The Community Complaint Information System in Jentera Stabat Village is a system built to facilitate the community in filing complaints regarding issues that occur in the village. This system is designed with the aim of improving public services and expediting the resolution of problems faced by the community. The system is equipped with features such as online complaint form filling, monitoring of complaint status, and notifications to relevant parties. The use of this system is expected to enhance transparency and accountability of the village government in handling community complaints. In its development, the system involves various stakeholders such as the community, village government, and system developers. With the implementation of this community complaint information system, it is hoped that the quality of public services will improve and the resolution of community issues will be expedited REFERENCES Faittullah Akbar, M. (2023). Penerapan Metode Waterfall pada Sistem Informasi Penjualan Dan Persediaan Pada Warung Makan Hejo Karawang. Indonesian Journal Computer Science, 2(1), 29–34. https://doi.org/10.31294/ijcs.v2i1.1902 Firgia, L., Muhamad Muslih, & Aditya Pratama. (2022). Implementasi Sistem Informasi Pengaduan Masyarakat Di Daerah Perbatasan Studi Kasus Desa Cipta Karya. Jurnal Rekayasa Teknologi Nusa Putra, 8(2), 101–110. https://doi.org/10.52005/rekayasa.v8i2.267 Fisa Wisnu Wijaya, & Lomban, D. (2022). Sistem Informasi Inventory Barang Menggunakan Metode Waterfall. Jurnal Informatika, Teknologi Dan Sains, 4(3), 247–254. https://doi.org/10.51401/jinteks.v4i3.1963 Haniva, D. T., Ramadhan, J. A., & Suharso, A. (2023). Systematic Literature Review Penggunaan Metodologi Pengembangan Sistem Informasi Waterfall, Agile, dan Hybrid. Journal of Information Engineering and Educational Technology, 7(1), 36–42. https://doi.org/10.26740/jieet.v7n1.p36-42 Harjono, W., & Kristianus Jago Tute. (2022). Perancangan Sistem Informasi Perpustakaan Berbasis Web Menggunakkan Metode Waterfall. SATESI: Jurnal Sains Teknologi Dan Sistem Informasi, 2(1), 47–51. https://doi.org/10.54259/satesi.v2i1.773 Irwanto. (2021). Perancangan Sistem Informasi Sekolah Kejuruan dengan Menggunakan Metode Waterfall (Studi Kasus SMK PGRI 1 Kota Serang-Banten). Lectura: Jurnal Pendidikan, 12(1), 399–405. Kurniasih, K., & Mulyono, H. (2022). Sistem Informasi Pengaduan Masyarakat Berbasis Web Pada Kantor Desa Ladang Peris Kecamatan Bajubang. Jurnal Manajemen Sistem Informasi, 7(4), 678–688. https://doi.org/10.33998/jurnalmsi.2022.7.4.692 Murdiani, D., & Sobirin, M. (2022). Perbandingan Metodologi Waterfall Dan RAD Dalam Pengembangan Sistem Informasi. JINTEKS (Jurnal Informatika Teknologi Dan Sains), 4(4), 302–306. Nugroho, F. E., Taufiq, R., & Alfarizi, M. S. (2021). RANCANG BANGUN SISTEM INFORMASI PELAYANAN PENGADUAN MASYARAKAT BERBASIS WEB PADA DESA SUKADAMAI KABUPATEN TANGERANG. Nurkholis, A., Susanto, E. R., & Wijaya, S. (2021). Penerapan Extreme Programming dalam Pengembangan Sistem Informasi Manajemen Pelayanan Publik. 5. Rohman, A., & Brilian, R. P. (2023). Sistem Informasi Manajemen Tabungan Pada Bank Sampah Raflesia Menggunakan Metode Waterfall. JBMI (Jurnal Bisnis, Manajemen, Dan …, 19(3), 192–204. https://doi.org/10.26487/jbmi.v19i3.25061 Supiyandi, S., Zen, M., Rizal, C., & Eka, M. (2022). Perancangan Sistem Informasi Desa Tomuan Holbung Menggunakan Metode Waterfall. JURIKOM (Jurnal Riset Komputer), 9(2), 274. https://doi.org/10.30865/jurikom.v9i2.3986 Syafiul Hamidani, Endang Etriyanti. (2022). Sistem Informasi Pengaduan Masyarakat Kota Lubuklinggau Berbasis Website. Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 3(2), 61–67. https://doi.org/10.52303/jb.v3i2.55 Usnaini, M., Yasin, V., & Sianipar, A. Z. (2021). Perancangan sistem informasi inventarisasi aset berbasis web menggunakan metode waterfall. Jurnal Manajemen Informatika Jayakarta, 1(1). Wau, K. (2022). Pengembangan Sistem Informasi Persediaan Gudang Berbasis Website Dengan Metode Waterfall. Jurnal Teknik, Komputer, Agroteknologi Dan Sains, 1(1), 10–23. https://doi.org/10.56248/marostek.v1i1.8 Zaenudin, A., & Syahidin, Y. (2022). Rancangan Sistem Informasi Pengaduan Masyarakat Berbasis Web Pada Kantor Kecamatan Dengan Fitur Notifikasi Telegram. Jutisi : Jurnal Ilmiah Teknik Informatika Dan Sistem Informasi, 11(1), 75. https://doi.org/10.35889/jutisi.v11i1.812